Realization of tunable elliptic low-pass filter based on CCCIIs - Kunto, Terdsak; Prommee, Pipat (My University, 2016)
This article presents a realization of electronically tunable current-mode Elliptic ladder low-pass filter using CCCIIs. The passive RLC ladder filters prototype and signal flow graph method (SFG) are employed for synthesis. The CCCII-based lossy, lossless integrators and current attenuator are required for the circuit realization. The proposed filter circuit can be electronically tuned between 1 kHz and 1 MHz through bias current from 0.05μA to 50μA. The proposed filter use ±1.5V power supply with 6 mW power consumption at 50 μA bias current. The proposed filter uses grounded capacitors without external resistors which is suitable for further integration. The total harmonic distortion (THD) of the low-pass filters is less than 0.5% over the operating frequency range. PSPICE simulation results are carried out, obtained by using BJT model parameter of HFA 3046, confirm the presented theory.
Keywords: current controlled conveyor; current mode; Elliptic; ladder filters